PENAHANAN ANAK YANG BERKONFLIK DENGAN HUKUM DALAM PERSPEKTIF HAK ASASI MANUSIA - Yudistira, Rizal; Suhartono, Slamet; Herlin Setyorini, Erny (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
â€Article 4 of the Child Protection Act that every child has the right to live, grow and participate properly and participate in accordance with human dignity and dignity, and get protection from violence and discrimination . The problem in this study is how the characteristics of children in conflict with the law can be detained. The research method used is normative legal research. "Legal research is a process to find the rule of law, legal principles, and legal doctrines in order to answer the legal issues at hand". The legislative approach method is used to understand the hierarchy of laws and principles contained in legislation. The law approach is carried out by examining all laws and regulations relating to the legal issues being addressed. The results of the study are an argument to solve the issue at hand. The conceptual approach is carried out when it does not depart from existing legal rules. This was done because there was indeed no or no legal rules for the problems faced "Against the perpetrators of child crime, which was detained by the police is a violation of human rights by depriving the freedom of children in conflict with the law. Children should get special treatment, not detention detention, but house arrest. Thus making children able to overcome their mistakes without feeling pressured by law enforcement.